Analysis of economy, energy efficiency, environment: A case study of the CHP system with both civil and industrial heat users - Congyu Wang; Jiwei Song; Wei Zheng; Zhaozhao Liu; Chengkun Lin (Case Studies in Thermal Engineering, 2022)
Integrated energy supply via the high-capacity combined heat and power (CHP) system is an effective way to achieve “win-win cooperation” for regional carbon reduction. A case study of the CHP system with both civil and industrial heat users is conducted to analysis the mixed impact of integrated energy supply on CHP systems. The steam-water equations and the off-design calculation model are developed to analyze the heat-power coupling mechanism of the CHP system. The linear-calculating diagram is obtained, which provides operational guidance for CHP system with simultaneous power, civil heat and industrial loads. Further, the analysis of economy, energy efficiency and environment within the operation region is performed. The results show that for a constant main steam flow rate, the industrial heat load is more profitable than the civil heat load. Moreover, the energy efficiency of the CHP unit can be further improved by undertaking the industrial heat load, despite at the expense of part capacity to supply civil heat. The average value of CO2 emissions per unit profit is reduced by approximately 7.69% overall after the stable industrial heat load of 100 MW, which means about 1.64 tons of CO2 can be reduced per 1000 USD profit.